An Analysis of Error in Undergraduate Students' Argumentative Essay Writing - Fatimah, Ariyani; Hasbullah, Hasbullah; Dabamona, Miftahulfadlik (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2025)
The main objective of this research is to know the common errors that the students in the batch 2020 of the English Education Department of Tarbiyah Faculty at IAIN Sorong made in Argumentative essay Writing. Theoretically, this research intends to identify, define, classify, and finally explain the cause of errors. The writer used the qualitative method in this research, where the researcher analyzed the students’ writing to know the types of errors they make most in their writing grammatically and to know the causes of errors. After that, the writer described the number of errors that the students made. For this research, the writer analyzed each student's writing, finds out and classifies the errors he or she made, and lists them in tables. Furthermore, from those errors, the writer concluded what the causes of those errors are. After analyzing the data, the researcher found that there are four types of errors made by the students to Dulay's Theory. First, the errors of Omission with a percentage of 39%, followed by Addition with a percentage of 19%, the errors of misformation with a percentage of 41%, and the last misordering with a percentage of 2% of 100% from all errors made by the students.